Challenges of HIV Self-Test Distribution for Index Testing When HIV Status Disclosure Is Low: Preliminary Results of a Qualitative Study in Bamako (Mali) as Part of the ATLAS Project - Boye, Sokhna; Bouaré, Seydou; Ky-Zerbo, Odette; Rouveau, Nicolas; Simo Fotso, Arlette; d'Elbée, Marc; Silhol, Romain; Maheu-Giroux, Mathieu; Vautier, Anthony; Breton, Guillaume; Keita, Abdelaye; Bekelynck, Anne; et al. (Frontiers in Public Health, 2021)
The rate of HIV status disclosure to partners is low in Mali, a West African country with a national HIV prevalence of 1.2%. HIV self-testing (HIVST) could increase testing coverage among partners of people living with HIV (PLHIV). This study aims to improve our understanding of the practices, limitations and issues related to the distribution of HIV self-tests at an HIV care clinic in Bamako, Mali. An ethnographic survey was conducted in 2019. It consisted of (i) individual interviews with 8 health professionals involved in the distribution of HIV self-tests; (ii) 591 observations of medical consultations, including social service consultations, with PLHIV; (iii) 7 observations of peer educator-led PLHIV group discussions. HIVST was discussed in only 9% of the observed consultations (51/591). When HIVST was discussed, the discussion was almost always initiated by the health professional rather than PLHIV. HIVST was discussed infrequently because in most of the consultations, it was not appropriate to propose partner HIVST (e.g., when PLHIV were widowed, did not have partners, or had delegated someone to renew their prescriptions). Some PLHIV had not disclosed their HIV status to their partners. Dispensing HIV self-tests was time-consuming, and medical consultations were very short. Three main barriers to HIV self-test distribution when HIV status had not been disclosed to partners were identified: (1) almost all health professionals avoided offering HIVST to PLHIV when they thought or knew that the PLHIV had not disclosed their HIV status to partners; (2) PLHIV were reluctant to offer HIVST to their partners if they had not disclosed their HIV-positive status to them; (3) there was limited use of strategies to support the disclosure of HIV status. In conclusion, it is essential to strengthen strategies to support the disclosure of HIV+ status. It is necessary to develop a specific approach for the provision of HIV self-tests for the partners of PLHIV by rethinking the involvement of stakeholders. This approach should provide them with training tailored to the issues related to the (non)disclosure of HIV status and gender inequalities, and improving counseling for PLHIV.